Planning of content of professionally pedagogical education of students of art creative specialities (Pedagogy of Higher and Secondary Education, 2022)
Planning of content of professionally pedagogical education of students of art creative specialities. In the article the features of professionally pedagogical education of students of creative higher educational establishment are examining, the criteria ofplanning of its maintenance are selecting.
Keywords: social-culture sphere; personality; professionally pedagogical preparation